Short report of first experiences in stabilization of fine road soils with shredded face masks in Argentina - Rivera, José Julián; Zapata Ferrero, Ignacio; Battista, Nicolás Daniel (My University, 2022)
The COVID-19 pandemic caused a disproportionate increase in the use of face masks. This generates an environmental threat because these face masks have become more in a household waste than a pathogenic one. From the LEMaC, a pre-feasibility analysis is generated at the laboratory level to use these residues, once shredded, in the stabilization of fine soils, for the constitution of improved subgrades and subbase layers in pavements. The mechanical results obtained are showed, to simplify the path of future related experiences. It is concluded that the optimal percentage of incorporation can be around 2% by weight, on 100% of the weight of dry soils. This can be extrapolated to other waste that is made with the same textile
Keywords: Shredded face masks; Roads; Argentina